Wood structure of trigonobalanus excelsa g. lozano-c., hdz-c. and amp; henao (fagaceae) (1980)
General characters: Hardly any differentiation in sapwood and heartwood. The wood greyish middle brown, with a reddish tinge. On the transverse surface growth rings not visible, the wide rays distinct with the naked eye as lighter coloured stripes. The grain straight, the texture rather fine; very hard and difficult to cut across the grain.